MP-1 Cysticercosis in Goats in the Semi-arid Tropics of Timor Island, East Nusa Tenggara, Indonesia - Aji Winarso; Mariany P A Tomonob; Victoriano King Dalman Mbula; Magdalena Olivia de Santo; Emi Liana Malingga (Hemera Zoa, 2018)
Semi-arid region of West Timor has a good potential of livestock farming, including goat farming. Small scale goat farms in West Timor raise their animals in semi-intensive system by rearing their animals in pasture or rice field. There are a high demand of goat in the local market especially prior to Kurban Fiest. Despite high population growth of goat, there are some reasons causing low productivity, such as parasite infections. Taeniid cestodes infect carnivores (as well as human) as the definitive host and involve a wide range of intermediate host where they present as metacestode cyst.1Cysticercosis or infection of cestode larval stages (metacestode) may appear vary from subclinical to severe clinical signs.1 Cysticercus infection lead to productivity losses2 even mortality in livestock.3 They are responsible for economic losses due to partial or total condemnation of carcass and offal.1, 3 Cysticercosis also pose a risk of public health.3 The zoonosis risk even higher in developing countries and especially in rural area, people lives in close proximity with animals, poor sanitation3 and low awareness. Dogs and wild canids are common definitive host of the most metacestodes occurring in goat and other ruminants.1 But some of them involve human as definitive host as well as incidental intermediate host in their life cycle.4 To make an effective control of cestode infection, it is necessary to identify the agent and collect its epidemiological data. This research aims to determine the prevalence and to identify the etiological agent of cysticercosis of goats in semi-arid region of West Timor.Cysticercosis in Goats in the Semi-arid Tropics of Timor Island, East Nusa Tenggara, Indonesia